2013
DOI: 10.1242/jeb.077644
|View full text |Cite
|
Sign up to set email alerts
|

Flexible strategies for flight control: an active role for the abdomen

Abstract: SUMMARYMoving animals orchestrate myriad motor systems in response to multimodal sensory inputs. Coordinating movement is particularly challenging in flight control, where animals deal with potential instability and multiple degrees of freedom of movement. Prior studies have focused on wings as the primary flight control structures, for which changes in angle of attack or shape are used to modulate lift and drag forces. However, other actuators that may impact flight performance are reflexively activated durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(128 citation statements)
references
References 32 publications
1
127
0
Order By: Relevance
“…Hawk moths exhibit another possible example of this principle in which fast antennal feedback adds linearly to slower visual feedback to regulate the stabilizing motion of the abdomen during hovering flight (24,51). In the present study, we have shown that flies use this same principle in the context of translational flight control, which involves different constraints.…”
Section: Discussionmentioning
confidence: 50%
“…Hawk moths exhibit another possible example of this principle in which fast antennal feedback adds linearly to slower visual feedback to regulate the stabilizing motion of the abdomen during hovering flight (24,51). In the present study, we have shown that flies use this same principle in the context of translational flight control, which involves different constraints.…”
Section: Discussionmentioning
confidence: 50%
“…Nor did that study investigate other possible reasons for the changes in abdomen pitch that many flying insects display. Furthermore, Dyhr et al (2013) proposed and confirmed, for hawkmoths (Manduca sexta), that pitch reorientation rotates the thorax, resulting in redirection of the flight force, and assists in flight stabilisation. Also, by measuring the pitch response to a vertically oscillating visual stimulus under open-loop conditions, they found that the pitch control system can be adequately modelled as a firstorder high-pass filter, with an additional pure time delay of 41 ms. Tanaka and Kawachi (2006) conducted similar tethered flight experiments on bumblebees (Bombus terrestris), where a visual grating (generated by a panoramic matrix of LEDs surrounding the insect) was oscillated vertically in a sinusoidal manner.…”
Section: Introductionmentioning
confidence: 93%
“…Such collaborations have, for example, led to the discovery of two independent mechanisms that animals can use to overcome the trade-off between stability and maneuverability in locomotion. Fish use mutually opposing forces (Sefati et al 2013), whereas insects accomplish the same ends using flexible airframes (Dyhr et al 2012(Dyhr et al , 2013. These collaborations also led to advances in engineering.…”
Section: Challenge 1: Understanding Living Organisms As Multiscale Symentioning
confidence: 99%
“…This knowledge stimulated engineers and material scientists to develop novel types of dry adhesives (Ge et al 2007, Lee HS et al 2007, Lee JH et al 2009, Murphy et al 2009, Filippov et al 2011. Such collaborations have also led to new insight regarding the dynamic control of animal locomotion (e.g., Libby et al 2012, Dyhr et al 2013, Mongeau et al 2013, Sefati et al 2013, and new strategies for controlling complex and highly dynamic machines (e.g., Dyhr et al 2012). Combined biology, applied mathematics, and engineering approaches are presently being used to examine the role of feedback in the stability (or change) of dynamical systems, such as regulatory gene networks, cellular metabolic systems, sensorimotor dynamics of moving animals, and even ecological or evolutionary dynamics of organisms and populations (Cowan et al 2014).…”
Section: New Opportunitiesmentioning
confidence: 99%